Designing an Eco-Friendly Information Center and Gallery for Sustainable Woven Fabrics in Jakarta - Izzati, Alifia Wida; Kurniawan, Rizki; Zahra Cyrilla , Lucy (Institut Seni Indonesia Surakarta, 2024)
The rapid growth of fast fashion has led to significant environmental damage. In contrast, Indonesia's traditional weaving industry represents a sustainable production method. However, local fabric brands emphasizing sustainability are not well-known. This study aims to design an information center and gallery to promote eco-friendly woven fabrics, utilizing sustainable materials such as bamboo, glass, and wood. The main objective is to raise public awareness of sustainable woven fabrics and support local brands with sustainable principles. A qualitative research approach was used, including data collection through questionnaires and surveys. Observations were made at the Textile Museum and Batik Keris to inform the design process. The design incorporates sustainable materials and aims to educate the public about environmentally friendly woven fabrics. The project includes spaces for workshops, information dissemination, and displays, promoting sustainable development goals and preserving Indonesian cultural heritage​.